2009
DOI: 10.1097/aln.0b013e3181b799ef
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Modeling of the Interaction between Propofol and Sevoflurane

Abstract: For both electroencephalographic suppression and tolerance to stimulation, the interaction of propofol and sevoflurane was identified as additive. The response surface data can be used for more rational dose finding in case of sequential and coadministration of propofol and sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 54 publications
2
37
0
1
Order By: Relevance
“…Even rather small deviations from constant relative potency can lead to curvilinear isobolograms (please see Curvilinear Isoboles) and worse, indeterminate solutions (please see Indeterminate Loewe Additvity Solutions). Without consideration of the individual dose-effect curves, deviations from the linear predictions indicate only that the two drugs are not identical and are not both agonists of a single receptor (139,155). They do not indicate that they are supra-additive or synergistic.…”
Section: Linear Isoboles Are a Raritymentioning
confidence: 99%
See 1 more Smart Citation
“…Even rather small deviations from constant relative potency can lead to curvilinear isobolograms (please see Curvilinear Isoboles) and worse, indeterminate solutions (please see Indeterminate Loewe Additvity Solutions). Without consideration of the individual dose-effect curves, deviations from the linear predictions indicate only that the two drugs are not identical and are not both agonists of a single receptor (139,155). They do not indicate that they are supra-additive or synergistic.…”
Section: Linear Isoboles Are a Raritymentioning
confidence: 99%
“…First, there is not sufficient mechanistic knowledge to enable quantitative predictions of the effects of drug combinations. If, for example, two drugs each bound reversibly to a single receptor with known kinetics and if the drugs' individual effects depended only on the number of receptors bound, then their individual and interactive effects could be computed using the laws of mass action (12,30,64,139,143,155). Similarly, interactive effects could be computed if they were shown to result directly from the frequency of action potentials in some accessible population of neurons.…”
Section: Mathematical Nature Of Synergymentioning
confidence: 99%
“…Schumacher et al [54 ] used response surface methodology to examine the influence of this interaction on the probability of tolerance of shake and shout and three noxious stimuli (tetanic stumulus, laryngeal mask insertion, laryngoscopy). They found that for both electroencephalographic suppression and tolerance to stimulation, the interaction of propofol and sevoflurane was additive.…”
Section: Pharmacodynamic Interactionsmentioning
confidence: 99%
“…The Ce50 SEVO for tolerance of LMA insertion and for laryngoscopy were also similar but substantially higher. In the previous study on the interaction of sevoflurane and propofol performed with the same stimuli by the same investigators, 10 the Ce50 values for sevoflurane for tolerance to shake and shout, tetanic stimulation, LMA insertion, and laryngoscopy were 1.03, 2.11, 2.55, and 2.83 vol.% respectively, which is markedly different from that found in the present study (1.47, 1.48, 2.09, and 2.00 vol.%, respectively). Furthermore, the slope reported by Schumacher et al was 17.6, whereas in the present study it was 7.41.…”
Section: Figmentioning
confidence: 99%
“…17 In the current data set it was observed in several cases that the patient was tolerant to a stimulus, whereas the same patient was responsive to the preceding, a priori considered less intense stimulus. Therefore the approach described by Bouillon et al 6 and by Schumacher et al, 10 combining the observed responses to the four stimuli into a single value, could not be applied. Instead the observed response to each stimulus was compared to the probability of that response according to the model, irrespective of the response to the other stimuli.…”
Section: Pharmacodynamic Analysis Of Quantal Responsesmentioning
confidence: 99%